Do Primary Healthcare Facilities in More Remote Areas Provide More Medical Services? Spatial Evidence from Rural Western China - Chi Shen; Sha Lai; Qiwei Deng; Dan Cao; Dantong Zhao; Yaxin Zhao; Zhongliang Zhou; Wanyue Dong; Xi Chen (Institute of Labor Economics (IZA), 2023)
Primary healthcare institutions (PHIs) in China have experienced a sizable decline in medical services in recent years. Despite the large regional disparities in China, there is a lack of evidence on the differential patterns of medical services offered by PHIs, especially from a spatial perspective. This study examines whether residents in more remote areas use more medical services offered by township healthcare centers (THCs), a main type of PHIs. Linking medical visits to 923 THCs in a western Chinese province in 2020 with the driving time and geographic coordinates from the Gaode map, a leading map navigation provider in China, we applied a multilevel linear model and a geographically weighted regression to examine spatial heterogeneity in medical service utilization. We showed that a one-hour increase in the shortest driving time between THCs and the local county hospitals was associated with an average 6% increase in THCs outpatient visits and a 0.6% increase in THCs inpatient visits. Our findings suggest that THCs located in more remote areas provided more medical services, especially outpatient services.
Keywords: I11; I14; I18; R53; 330; primary healthcare institutions; spatial accessibility; disparities; medical service; China